2020
DOI: 10.29333/ejgm/7903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Clinical Scenario-Based Educational Workshop and Reflection on the Knowledge and Attitude of Head Nurses and Clinical Supervisors toward in the Brain Death and Organ Donation

Abstract: Background: Participation in the organ donation process is a part of the expected activities in the nursing profession and nurses play a major role in this regard. Providing correct information by nurses increases the number of organ donors and it requires knowledge and positive attitude towards organ donation. The present study was conducted with the aim of evaluating the effect of clinical scenario-based educational workshop and rethinking on the knowledge and attitude of head nurses and clinical supervisors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…69 Table 3 illustrates 25 empirical studies retrieved that examined HCP understanding of BD. Twenty studies used a quantitative approach 53,68-86 and 3 used a qualitative approach. 73,87,88 Only 2 studies reported conducting literature reviews to illustrate gaps in HCPs understanding of death and death determination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…69 Table 3 illustrates 25 empirical studies retrieved that examined HCP understanding of BD. Twenty studies used a quantitative approach 53,68-86 and 3 used a qualitative approach. 73,87,88 Only 2 studies reported conducting literature reviews to illustrate gaps in HCPs understanding of death and death determination.…”
Section: Resultsmentioning
confidence: 99%
“…73,76,77,81,82 Formal training is shown to correlate with improved attitudes and knowledge of BD. 69,84…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation